Implementing Mixed Method of Peer Teaching and Problem Solving on Undergraduate Students - Firli, A.; Rismayani, R.; Sitorus, P.M.T.; Manuel, B. (Journal of Education Reseach and Evaluation, 2017)
This study examined the application of problem solving method combined with student centered learning (peer teaching) method as a mixed method to improve student’s passing level of financial management course. The object of this study was the 84 students of financial management course separated within two classes during the odd semester period 2014/2015, July until December 2015 with fourteen meeting courses. Data used to measure the results of the application is mid and final exam scores of both classes. Researcher used observation, interview and documentation as data collect technique also triangulation technique as data validity check. This study used problem solving method combined with student centered learning (peer teaching) method as a mixed method which included into the Classroom Action Research. The final results show the increase in class A passing level is 17%. Class B passing level increased 3%. From the research we also know that in practical use of mixed method learning, leader’s quality and conducive learning environment are influencing factors in improving student’s learning performance. While the result confirms that mixed method improving learning performance, this study also founds additional factors that might be considerably affecting the results of learning performance when implementing the mixed method.